2003
DOI: 10.1523/jneurosci.23-04-01506.2003
|View full text |Cite
|
Sign up to set email alerts
|

Slow Na+Inactivation and Variance Adaptation in Salamander Retinal Ganglion Cells

Abstract: The retina adapts to the temporal contrast of the light inputs. One component of contrast adaptation is intrinsic to retinal ganglion cells: temporal contrast affects the variance of the synaptic inputs to ganglion cells, which alters the gain of spike generation. Here we show that slow Na+ inactivation is sufficient to produce the observed variance adaptation. Slow inactivation caused the Na+ current available for spike generation to depend on the past history of activity, both action potentials and subthresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 38 publications
5
111
0
2
Order By: Relevance
“…2) (Kim and Rieke, 2001;Zaghloul et al, 2005). This intrinsic mechanism, in salamander, could be explained by slow inactivation of sodium channels (Kim and Rieke, 2003). A similar mechanism may underlie the intrinsic mechanism for gain control in mammalian cells.…”
Section: Two Spatial Mechanisms For Contrast Gain Control In Ganglionmentioning
confidence: 94%
“…2) (Kim and Rieke, 2001;Zaghloul et al, 2005). This intrinsic mechanism, in salamander, could be explained by slow inactivation of sodium channels (Kim and Rieke, 2003). A similar mechanism may underlie the intrinsic mechanism for gain control in mammalian cells.…”
Section: Two Spatial Mechanisms For Contrast Gain Control In Ganglionmentioning
confidence: 94%
“…Experiments have shown that slow inactivation of sodium channels induces slow modulations in the responsiveness of neurons to inputs (Fleidervish et al, 1996;Kim and Rieke, 2003). In general, excitability depends on many variables, for example, the availability of many different ion channel types or the level of calcium.…”
Section: Defining the Neuronal Excitability Variablementioning
confidence: 99%
“…Several underlying molecular mechanisms support these modulations in an activity-dependent manner (LeMasson et al, 1993;van Ooyen, 1994;Marom, 1998;Wang, 1998;Carr et al, 2003). Such mechanisms are usually understood to operate by adding uniquely defined slow time scales (Marom and Abbot, 1994;Fleidervish et al, 1996;Kim and Rieke, 2003) and cannot capture multiple-time-scale dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation induced by slow intrinsic ionic currents of the spike generator is, however, also commonly observed in neurons and may enhance their response to highfrequency input French et al, 2001), mask low-intensity stimuli (Sobel and Tank, 1994;Wang, 1998), induce contrast adaptation (Sanchez-Vives et al, 2000), remove temporal correlations from the input (Wang et al, 2003), or affect network synchrony and rhythms (Crook et al, 1998;Ermentrout et al, 2001;van Vreeswijk and Hansel, 2001;Fuhrmann et al, 2002). Because adaptation usually operates within complex neural circuits and on many different time scales (Fairhall et al, 2001;Baccus and Meister, 2002;Kohn and Whitsel, 2002), it has been difficult to determine how these different cellular mechanisms contribute to network-level computations [e.g., sensory adaptation (Chung et al, 2002;Castro-Alamancos, 2004) or contrast adaptation (Sanchez-Vives et al, 2000;Fairhall et al, 2001;Kim and Rieke, 2003) in the visual system]. There are few studies on the functional role of adaptation or synaptic depression within a behavioral context (Sobel and Tank, 1994;Cook et al, 2003;Luksch et al, 2004;Ronacher and Hennig, 2004).…”
Section: Introductionmentioning
confidence: 99%